Performance and physiological effects of different descending strategies for cross-country mountain biking - Miller, M. C.; Macdermid, P. W.; Fink, P. W.; Stannard, S. R. (European Journal of Sport Science, 2017)
This study investigated the performance-related feasibility and physiological benefits of purposefully eliminating propulsive work while descending in mountain biking and compared values to those measured during road descending. Participants cycled uphill on a road at race pace before descending over three conditions (off-road pedalling; off-road coasting; road coasting). Relatively low power output during off-road pedalling was associated with a greater oxygen uptake (p < .01) when compared with off-road coasting despite no difference in vibration exposure (p > .05). Importantly, pedalling did not invoke a performance benefit (p > .05) on the descent used in this study. Significantly greater heart rate and oxygen uptake (both p < .01) were observed between road and off-road descending, likely caused by the increase in terrain-induced vibrations (p < 0.1) experienced between the bicycle and rider. Results indicate that reducing propulsive work during descending can improve recovery without being disadvantageous to performance. Similarly, the vibrations experienced during road descending are relatively low, and further reduce oxygen cost. In an effort to increase efficiency, it is recommended that mountain bike athletes focus on skills to increase descending speed without the addition of pedalling, and that equipment be used to decrease vibrations nearer to those seen on the road.